APPLICATION OF ACTIVE KNOWLEDGE SHARING STRATEGY ASSISTED BY GOOGLE CLASSROOM APPLICATION ON STUDENT LEARNING OUTCOMES ON VIRUS MATERIAL - M. Rizki Samsil Ardi; Dewi Cahyani (Jurnal IPA Terpadu, 2024)
This research aims to determine the significant influence of the application of Active Knowledge Sharing learning strategies on students' cognitive abilities in Biology subjects at SMAN 1 Tanjung Brebes. This research is quasi-experimental with nonequivalent control group design. The subjects are teachers and students, while the object is the application of Active Knowledge Sharing strategies to student learning outcomes. The population was all 288 students in class X of SMAN 1 Tanjung Brebes. The sample was 36 students in class X.2 as the experimental class and 36 students in class X.1 as the control that selected by purposive sampling method. The data collection techniques used are observation, questionnaires, documentation and tests. Based on the results, it was found that the cognitive abilities of students in the experimental class that used Active Knowledge Sharing strategies were higher than those in the control class that used conventional learning. This is proven through t test which shows that  that there is a difference in improving student learning outcomes between classes that use Active Knowledge Sharing strategies assisted by Google Classroom and classes that do not use Active Knowledge Sharing learning strategies at SMA Negeri 1 Tanjung Brebes in biology learning virus material.